JUAL BELI UANG (FOREIGN EXCHANGE TRANSACTION) DITINJAU DARI HUKUM EKONOMI ISLAM - Kholidah Kholidah (Yurisprudentia: Jurnal Hukum Ekonomi, 2022)
Foreign exchange trading transactions are getting more and more in demand, Muslim investors/traders are no exception. Even recently, forex trading has been used as a speculation tool for traders to make a profit. Therefore, forex trading has become an important issue and has become a sharp focus for Muslim scholars and economists. In the study of fiqh, foreign exchange trading is known as al-sharf, namely buying and selling naqdain, gold for gold, silver for silver, or one of the two. This transaction is basically justified in Islam as long as it does not contain elements of usury. But unfortunately, the practice of foreign exchange trading is full of elements of usury, speculation, and gambling. According to the scholars, of these four forms of activity, only spot transactions are permitted, while forward, swap and option forms are prohibited.